Charting the ‘Voyage’ of Squatter Housing in Urban Spatial ‘Quadruped’ - Tansı Şenyapılı (European Journal of Turkish Studies)
Sufficient time has expired to look back and chart the ‘voyage’ of the two components of squatter housing phenomenon; the shelter and its builders/inhabitants in time. Both have gone through radical transformations in a period of half a century. This study includes one such attempt. The basic assumption is that; of the two components, the shelter is the variable, dependent on the builders/inhabitants’ position, role and function in the labour market which constitutes the independent variable. This assumption is discussed in an urban spatial quadruped (three abstract, relation-based, economic, political and social spaces, and the physical urban space) displaying chronological ‘refractions’ with reference to different development models adopted in Turkey.